Prioritizing the Logistics Management Factors Affecting Company Performance: Case Study of ADNOC - Abdulla, Mohamed Fuad Mohamed Hassan; Musa, Haslinda (International Journal of Sustainable Construction Engineering and Technology, 2022)
This paper presents a study to prioritize the logistics management factors influencing the performance of the oil and gas industry in the UAE. The study discovered 56 logistic elements classified into seven groups: Logistics Information System; Transport Management; Inventory Management; Order Process Management; Information Flow Management; Logistics Agility; and Logistics Integration Capabilities. To rank these factors, Abu Dhabi National Oil Company (ADNOC) employees completed a questionnaire survey. The survey data was analysed descriptively, and the elements were ranked based on the mean score and standard deviation of each individual factor. According to the findings, the most critical logistic factor for the Logistics Information System (LIS) group is the accuracy of the logistics information system. The most critical logistic factor for the Transport Management (TM) group is Routing and scheduling; the most important logistic factor is size requirements for the Inventory Management (IM) group. The most critical logistic factor for the Order Process Management (OPM) group is top management support, while for the Information Flow Management (IFM) group; the most critical logistic factor is quantifying the level of detail of information packages. The Agility of Logistics Service (ALS) group is increasing the speed of the supply chain to improve customer service. Finally, the Logistics Integration Capabilities (ICL) group shares service information with LSSC members. These findings will be useful in assisting logistics parties in improving their services for the benefit of the company’s performance.